Tea consumption and cancer: a Mendelian randomization study - Chunyu, L; Si, C; Yuanjie, P; Canqing, Y; Dianjianyi, S; Pei, P; Junshi, C; Chen, ZM; Jun, L; Liming, L (Chinese Medical Association, 2023)
Objective A Mendelian randomization (MR) analysis was performed to assess the relationship between tea consumption and cancer. Methods There were 100 639 participants with the information of gene sequencing of whole genome in the China Kadoorie Biobank. After excluding those with cancer at baseline survey, a total of 100 218 participants were included in this study. The baseline information about tea consumption were analyzed, including daily tea consumption or not, cups of daily tea consumption, and grams of daily tea consumption. We used the two-stage least square method to evaluate the associations between three tea consumption variables and incidence of cancer and some subtypes, including stomach cancer, liver and intrahepatic bile ducts cancer, colorectal cancer, tracheobronchial and lung cancer, and female breast cancer. Multivariable MR and analysis only among nondrinkers were used to control the impact of alcohol consumption. Sensitivity analyses were also performed, including inverse variance weighting, weighted median, and MR-Egger. Results We used 54, 42, and 28 SNPs to construct non-weighted genetic risk scores as instrumental variables for daily tea consumption or not, cups of daily tea consumption, and grams of daily tea consumption, respectively. During an average of (11.4±3.0) years of follow-up, 6 886 cases of cancer were recorded. After adjusting for age, age 2, sex, region, array type, and the first 12 genetic principal components, there were no significant associations of three tea consumption variables with the incidence of cancer and cancer subtypes. Compared with non-daily tea drinkers, the HR (95% CI) of daily tea drinkers for cancer and some subtypes, including stomach cancer, liver and intrahepatic bile ducts cancer, colorectal cancer, tracheobronchial and lung cancer, and female breast cancer, are respectively 0.99 (0.78-1.26), 1.17 (0.58-2.36), 0.86 (0.40-1.84), 0.85 (0.42-1.73), 1.39 (0.85-2.26) and 0.63 (0.28-1.38). After controlling the impact of alcohol consumption and performing multiple sensitivity analyses, the results were similar. Conclusion There is no causal relationship between tea consumption and risk of cancer in population in China.